Handbook of Manufacturing Systems and Design An Industry 4.0 Perspective - Zaman, Uzair Khaleeq uz; SIADAT, Ali; Ahmed Baqai, Aamer; Naveed, Kanwal; kumar, atal anil (Taylor & Francis, 2024)
This handbook provides a comprehensive overview of manufacturing systems, their role in product/process design, and their interconnection with Industry 4.0 perspective, especially related to design, manufacturing, and operations. Handbook of Manufacturing Systems and Design: An Industry 4.0 Perspective presents theories and concepts of Industry 4.0, with a focus on the different types of manufacturing systems, associated design, and control strategies. It concentrates on the operations in Industry 4.0, emphasizing supply chain, logistics, risk management, and reverse engineering perspectives. Offering basic concepts and applications through to advanced topics, the handbook is a comprehensive source of knowledge as well as a vehicle to explore the future possibilities of design, techniques, methods, and operations associated with Industry 4.0. Concepts with practical applications in the form of case studies are added to each chapter to round out the many attributes this handbook offers. This handbook targets students, engineers, managers, designers, and manufacturers. It will assist in their understanding of the core concepts of manufacturing systems in connection with Industry 4.0 and optimize alignment between supply and demand in real-time for effective implementation of the design concepts.